Strength test of ship superstructure opening group structures and equivalent loading methods for external pressure - Zijian HU; Zhengze XIA; Changhai CHEN; Yuansheng Cheng; Jun Liu (Zhongguo Jianchuan Yanjiu, 2021)
ObjectivesAiming at exploring the influence of external pressure loading on the stress calculation results of the opening group structures of ship superstructures, a study on external pressure loading methods and strength tests is carried out.MethodsFirst, a three-dimensional airtight superstructure model with opening groups is made on which strength tests are done through internal vacuum extraction to simulate external pressure loading. Numerical simulation analysis is then carried out to study the stress distribution of typical locations in the superstructure under different equivalent loadings (i.e., equivalent point, linear and surface loadings). A comparison of stress levels between the test results and simulation obtained from different loading methods is done to explore the influence of loading point spacing on the stress distribution of opening group structures via equivalent multi-point loading.ResultsThe results show that equivalent elastic surface and linear loading are in good agreement with the actual external pressure loading. When the ratio of loading point spacing to opening circumference reaches 0.074, the stress levels of the measuring points predicted via the equivalent point loading method correlate well with the test results. The relative average error between the stress levels of the measuring points predicted via the equivalent rigid surface loading method and test results is much greater.ConclusionsThe equivalent elastic surface, linear and point loading methods with a certain density can simulate the actual external pressure loading well, while the equivalent rigid surface loading method causes the stress levels at the corners of the openings or middle points of the edges to be extremely low.